Application of the Vivaldi Antenna in a Linear Antenna Array for Radar Systems - Marian Wnuk (Scientific Journal of Gdynia Maritime University)
The article presents a new broadband TSA antenna with a widening aperture, which is to be the basic radiating element in a multi-element antenna. The TSA antenna is characterized by a low-value standing wave ratio (SWR) covering the widest possible frequency band while maintaining a symmetrical and directional radiation pattern. The design was created using the WIPL-D computer program. This program enabled a computer simulation and the selection of the final solution. The "output" model is a radiator powered by a half-wave dipole. The results include the computer simulations of multi-element antennas, as well as the physical measurements carried out in an anechoic chamber for various configurations of antenna arrays. The discussion includes a number of significant problems that arise in the construction of antenna arrays, their various solutions, while the method of their power supply, as carried out in this paper, requires obtaining a bandwidth of 700–800 kHz for the SWR < 2 criterion (for radar applications this criterion is the more stringent SWR < 1, 3).